Coexistence, Unity, Professionalism and Prudence - Gallo, Miguel Angel (European Journal of Family Business, 2021)
Family firms are complex and dynamic entities that are rich with peculiar, idiosyncratic features. The objective of this paper is to provide guidance to help those involved in family businesses, businesspersons, and family members to pursue the continuity of the family firm over time. Based on the author’s experience with entrepreneurs who built successful businesses, this paper identifies four elements that are critical to achieve transgenerational continuity in family firms, namely: coexistence, unity, professionalism, and prudence. The analysis of each element provides suggestions and key considerations for both scholars and practitioners in the family business field.